An evaluation of the quality of services provided in leader training centers using the SERVQUAL scale and the 5 GAPS mode - Stefano, N. (2021)
Fil: Stefano, N. Universidade Federal de Santa Maria. Programa de Pós-Graduação em Engenharia de Produção; Brasil.